What is Digital Journalism Studies? - Steensen, Steen and Westlund, Oscar (Taylor & Francis, 2021)
What is Digital Journalism Studies? delves into the technologies, platforms, and audience relations that constitute digital journalism studies’ central objects of study, outlining its principal theories, the research methods being developed, its normative underpinnings, and possible futures for the academic field. The book argues that digital journalism studies is much more than the study of journalism produced, distributed, and consumed with the aid of digital technologies. Rather, the scholarly field of digital journalism studies is built on questions that disrupt much of what previously was taken for granted concerning media, journalism, and public spheres, asking questions like: What is a news organisation? To what degree has news become separated from journalism? What roles do platform companies and emerging technologies play in the production, distribution, and consumption of news and journalism? The book reviews the research into these questions and argues that digital journalism studies constitutes a cross-disciplinary field that does not focus on journalism solely from the traditions of journalism studies, but is open to research from and conversations with related fields. This is a timely overview of an increasingly prominent field of media studies that will be of particular interest to academics, researchers, and students of journalism and communication.
https://katalog.adlr.link/Record/26-27307